Suffering and Healing, Subordination and Power: Women and Possession Trance - Bourguignon, Erika (Ethos, 2004)
This article is an argument that for women, possession trance constitutes a psychodynamic response to powerlessness by providing them a means for the gratification of wishes ordinarily denied to them. Powerful alters enable them to act out wishes they cannot express directly. Possession serves both as an idiom of distress and of indirect self-assertion, facilitated by ritualized, culturally structured dissociation.